Analisis Hubungan Kepercayaan Diri dengan Pengambilan Keputusan di Unit Kegiatan Mahasiswa Bola Basket Institut Teknologi Bandung - Dhea Mahsa; Yusuf Hidayat; Salman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Decision-making is a critical aspect determining how well basketball athletes perform when facing in-game situations. Self-confidence is considered one of the psychological factors potentially linked to this ability. This study examines the association between confidence and decision-making among members of the Bandung Institute of Technology (ITB) Basketball student club, using a quantitative correlational design. Thirty club members were involved through a total sampling technique. Data were gathered using a confidence questionnaire alongside the Decision Styles Questionnaire (DSQ), then analyzed in IBM SPSS Statistics through descriptive statistics, normality and linearity testing, Pearson Product Moment correlation, and a determination coefficient analysis. The findings show: (1) the data were normally distributed and linearly related; (2) the correlation analysis yielded r = 0.306 with p = 0.100 (p > 0.05), indicating no statistically significant link between confidence and decision-making; (3) the determination coefficient revealed that confidence accounted for only 9.3% of decision-making variance; (4) the remaining 90.7% was explained by other factors such as tactical knowledge, competitive experience, and match conditions. Confidence therefore does not appear to be the primary driver of decision-making quality among ITB Basketball club members. Keywords: Basketball, Self-Confidence, Decision Making